Imposed work of breathing of 16 neonatal CPAP-devices using different mechanisms of CPAP generation - Sterzik, Hanna; Arand, Joerg; Schwarz, Christoph; Kumpf, Matthias; Wald, Martin; Kribs, Angela; Lauth, Wanda; Gross, Maximilian; Poets, Christian F.; Haase, Bianca (Pediatric research, 2025)
Failure of continuous positive airway pressure (CPAP) in preterm infants may result from respiratory exhaustion, potentially also evoked by the CPAP device’s imposed work of breathing (iWOB). This study investigated in-vitro the iWOB of 16 CPAP-devices in four simulated neonatal scenarios with focus on the impact of different mechanisms of CPAP-generation.